Balance between Transmitter Availability and Dopamine D2 Receptors in Prefrontal Cortex Influences Memory Functioning. (2nd September 2019) - Papenberg, Goran; Karalija, Nina; Salami, Alireza; Rieckmann, Anna; Andersson, Micael; Axelsson, Jan; Riklund, Katrine; Lindenberger, Ulman; Lövdén, Martin; Nyberg, Lars; Bäckman, Lars
Abstract: Insufficient or excessive dopaminergic tone impairs cognitive performance. We examine whether the balance between transmitter availability and dopamine (DA) D2 receptors (D2DRs) is important for successful memory performance in a large sample of adults ( n  = 175, 64–68 years). The Catechol-O-Methyltransferase polymorphism served as genetic proxy for endogenous prefrontal DA availability, and D2DRs in dorsolateral prefrontal cortex (dlPFC) were measured with [ 11 C]raclopride-PET. Individuals for whom D2DR status matched DA availability showed higher levels of episodic and working-memory performance than individuals with insufficient or excessive DA availability relative to the number of receptors. A similar pattern restricted to episodic memory was observed for D2DRs in caudate. Functional magnetic resonance imaging data acquired during working-memory performance confirmed the importance of a balanced DA system for load-dependent brain activity in dlPFC. Our data suggest that the inverted-U–shaped function relating DA signaling to cognition is modulated by a dynamic association between DA availability and receptor status.